The academic competence development of Arabic lecturers in lecture management in Indonesia - Sulaiman, Fithriani, Fajriah,; ., Jabaliah (Opción, 2020)
This study focused on examining three issues: (1) the academic competence of Arabic lecturers in lecture management at the Tarbiyah and Teachers Training Faculty (TTF); (2) the strategies in developing the academic competence of Arabic lecturers at the TTF of The State Islamic University in Indonesia; and (3) the obstacles in developing the academic competence of Arabic lecturers at the TTF of the State Islamic University in Indonesia. The results showed that the lecturers assigned to the ASP at the TTF of the State Islamic University in Indonesia had effective academic competencies in the planning, implementation, and evaluation of lectures.